Bifunctional Cobalt‐Doped ZnIn2S4 Hierarchical Nanotubes Endow Noble‐Metal Cocatalyst‐Free Photocatalytic H2 Production Coupled with Benzyl Alcohol Oxidation. Issue 6 (6th March 2022) - Xue, Jierui; Liu, Huanhuan; Zeng, Suyuan; Feng, Yafei; Zhang, Yangyang; Zhu, Yin; Cheng, Mingyu; Zhang, Huaikun; Shi, Liang; Zhang, Genqiang
Abstract : Noble metals are widely used as cocatalysts to enhance the performance of photocatalysts, while large‐scale applications of noble metals are restricted due to their scarcity and high cost. In this context, it is an urgent task to design efficient noble‐metal cocatalyst‐free photocatalysts. Herein, the rational design and self‐sacrificial template‐assisted synthesis of cobalt‐doped ZnIn2 S4 hierarchical nanotubes (Co‐ZIS HNTs) are presented that can act as a bifunctional photocatalyst for H2 evolution and benzaldehyde production. Comprehensive experimental results indicate that the Co‐ZIS HNTs can lead to the enhanced separation and transfer efficiency of photoinduced carriers. As a result, the Co‐ZIS HNTs exhibit a 1.93 times higher H2 evolution rate than undoped ZnIn2 S4 microspheres (ZIS MSs) without any cocatalysts. Impressively, the Co‐ZIS HNTs show remarkable bifunctial photocatalytic activity toward both H2 evolution and benzyl alcohol oxidation. The extraordinary production rates of H2 and benzaldehyde are 2823.7 and 2769.0 μmol h −1  g −1, which are 7.44 and 7.60 times higher than that of bare ZIS MSs under visible light, respectively. This work not only proposes a promising strategy to devise highly active cocatalyst‐free photocatalysts, but also illustrates the potential for H2 evolution coupled with add‐valued products. Abstract : Hierarchical Co‐doped ZnIn2 S4 nanotubes can act as a bifunctional photocatalyst for H2 evolution coupled with benzyl alcohol oxidation, delivering impressive photocatalytic performance without cocatalysts.